The Relationship between Job Demands and Work Engagement among Employees - Adinda Ulina Siahaan; Mukhaira El Akmal; Astria Gres Naibaho; Jamar Gitari Yapen; Muhammad Zidan Yusra Malay; Rianda Elvinawanty (LifeSciFi, 2026)
This study is grounded in the importance of work engagement in enhancing employee performance, as well as the observed phenomenon of low engagement potentially influenced by job demands. The objective of this research is to examine the relationship between job demands and work engagement among employees. A quantitative approach with a correlational design was employed, involving 110 employees selected through a total sampling technique. Data were collected using Likert-scale questionnaires measuring job demands and work engagement, and subsequently analyzed using the Pearson Product-Moment correlation method. The findings indicate a significant negative relationship between job demands and work engagement, suggesting that higher job demands are associated with lower levels of employee engagement. Additionally, most employees demonstrated high levels of work engagement alongside relatively low to moderate job demands, indicating that existing work demands remain within manageable limits. The implications of this study highlight the importance of effectively managing job demands to foster higher levels of employee engagement. In conclusion, appropriate regulation of job demands plays a crucial role in maintaining and enhancing work engagement, which in turn contributes to improved productivity and overall organizational performance.